REPRESENTACIONES DEL GRUPO SIMÉTRICO CON MATRICES ENTERAS - Novoa Ramírez, Jesús Fernando; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2013)
Representations of the symrnetric group is one of the rnost fertile tapies in abstract algebra toda y. Spectral analysisfor experimental design, comrnunication network design, coding theory, are among the fields of application forthis theory. Despite this concept is very useful, it is hard to find a didactic too! that allow to professors andstudents to perform new examples, computations and verifications of the theoretical statements, lirniting thenumber of examples to the trivial ones, that do not reach neither the depth of the concept nor the complexity of thecomputation. Our aim with this paper is to presenta computer prograrn running on the CoCoA system, for computingirreducible representation matrices of the symmetric group with en tries on the integers